Applications of porous frameworks in solid‐phase microextraction. Issue 6 (25th January 2021) - Khataei, Mohammad Mahdi; Yamini, Yadollah; Shamsayei, Maryam
Abstract: Porous frameworks are a term of attracting solid materials assembled by interconnection of molecules and ions. These trendy materials due to high chemical and thermal stability, well‐defined pore size and structure, and high effective surface area gained attention to employ as extraction phase in sample pretreatment methods before analytical analysis. Solid‐phase microextraction is an important subclass of sample preparation technique that up to now different configurations of this method have been introduced to get adaptable with different environments and analytical instruments. In this review, theoretical aspect and different modes of solid‐phase microextraction method are investigated. Different classes of porous frameworks and their applications as extraction phase in the proposed microextraction method are evaluated. Types and features of supporting substrates and coating procedures of porous frameworks on them are reviewed. At the end, the prospective and the challenges ahead in this field are discussed.